2010
DOI: 10.1182/blood-2010-03-274571
|View full text |Cite
|
Sign up to set email alerts
|

In anemia of multiple myeloma, hepcidin is induced by increased bone morphogenetic protein 2

Abstract: Hepcidin is the principal iron-regulatory hormone and a pathogenic factor in anemia of inflammation. Patients with multiple myeloma (MM) frequently present with anemia. We showed that MM patients had increased serum hepcidin, which inversely correlated with hemoglobin, suggesting that hepcidin contributes to MMrelated anemia. Searching for hepcidininducing cytokines in MM, we quantified the stimulation of hepcidin promoterluciferase activity in HuH7 cells by MM sera. MM sera activated the hepcidin promoter sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 34 publications
9
111
0
3
Order By: Relevance
“…[33] Another study found more BMP-2 in sera from multiple myeloma patients than in normal sera, but still at low levels (~ 60 pg/mL). [38] We found increased levels of BMP-9 in myeloma sera compared to normal sera. [35] However, the total BMP-activity in the bone marrow niche of multiple myeloma patients, as measured by in situ SMAD1/5/8-phosphorylation, is not known.…”
Section: Expression Of Components Of the Bmp Signaling Pathwaymentioning
confidence: 59%
See 1 more Smart Citation
“…[33] Another study found more BMP-2 in sera from multiple myeloma patients than in normal sera, but still at low levels (~ 60 pg/mL). [38] We found increased levels of BMP-9 in myeloma sera compared to normal sera. [35] However, the total BMP-activity in the bone marrow niche of multiple myeloma patients, as measured by in situ SMAD1/5/8-phosphorylation, is not known.…”
Section: Expression Of Components Of the Bmp Signaling Pathwaymentioning
confidence: 59%
“…[84] BMP-2, -4, -6, and -9 all stimulated HAMP promoter activity in vitro whereas TGF-beta did not. [38] Thus, the conclusion drawn from this work was that BMP-2 was the main mediator of hepcidin induction in sera from myeloma patients. Targeting BMP-2 or other BMPs with the intention to treat anemia of multiple myeloma may not be a good approach, considering that there is substantial redundancy in the system regulating hepcidin.…”
Section: Bmp and Hepcidin-related Anemia In Multiple Myelomamentioning
confidence: 74%
“…Mice lacking HFE (64) or both HFE and TFR2 (65) are able to mount an appropriate immune response to LPS, but do not elevate hepcidin production nor develop hypoferremia. Furthermore, concomitant stimulation of both the BMP/SMAD and the JAK1/2-STAT3 pathways in rodents causes, at minimum, additive, and also in some experiments synergistic, effects upon up-regulation of hepcidin (59,66,67). In toto, this research suggests that the BMP/SMAD and JAK1/2-STAT3 signaling pathways impinge on one other, leading to increased hepcidin expression under conditions of infection or inflammation.…”
Section: Cooperation Between Bmp/smad and Jak1/2-stat3 Inflammatory Smentioning
confidence: 73%
“…Hepcidin is also greatly increased in multiple myeloma, a plasma cell malignancy that is thought to account for a large percentage of hematologic cancers (85). Hepcidin induction in this cancer requires BMP2, another BMP/SMAD pathway ligand, and the inflammatory cytokine IL-6 (67). Furthermore, recent work demonstrated that hepcidin is elevated in breast cancer patients and that diminished tumor expression of ferroportin promotes breast cancer growth (86,87).…”
Section: Other Causes Of the Anemia Of Inflammationmentioning
confidence: 99%
“…2002; Weiss and Goodnough 2005;Maes et al 2010), we analyzed serum hepcidin levels in HF and anemia patients without chronic disease. In this series of HF patients without chronic disease, serum hepcidin levels were higher in LC patients than those in patients without LC; namely, hepcidin levels of LC patients did not decrease despite low Hb levels.…”
Section: Anemia and Hepcidin In Hf Patientsmentioning
confidence: 99%